An In Vitro System That Simulates Plant Cell Extension Growth - Rayle, David L. (1970)
A new technique is described for studying controlled in vitro extension of plant cell walls. This technique uses frozen-thawed Avena coleoptile segments in which turgor is replaced by a constant applied force. In this system rapid extension is induced by low pH (3.0-3.6) but not by auxins or CO(2). Extensions of over 30% have been achieved. Our results indicate that cell wall synthesis is not required for rapid cell extension, and suggest that wall extension may be controlled by acid-labile, alkali-stable cell wall bonds.